Effects of waterborne exposure to 17β-estradiol and 4-tert-octylphenol on early life stages of the South American cichlid fish Cichlasoma dimerus - Meijide, Fernando Javier (2015)
Estrogenic chemicals are often detected in the aquatic environment and can negatively affect animal development and reproduction. In teleost fishes, the hormonal regulation during a critical period of larval development has a strong influence on gonadal sex differentiation; thus this process may be affected by the exposure to environmental estrogens. In this study, we first assessed the lethal acute toxicity of the natural estrogen 17β-estradiol (E2) and the weaker estrogen mimics 4-tert-octylphenol (OP) and 4-nonylphenol (NP) on larval stages of the South American cichlid fish Cichlasoma dimerus. In a further experiment, we analyzed the effects of chronic waterborne exposure to E2 and OP on gonad development and sex differentiation. Exposure to high concentrations of E2 had a pronounced feminizing effect directing sex differentiation towards ovarian development, while testis development was inhibited at a lower, environmentally relevant concentration. Among OP-exposed fish, 15–38.5% of the males exhibited testicular oocytes (TOs), a commonly reported biomarker of estrogenic exposure. However, since TOs were also recorded in control males and the proportion of males with TOs was not significantly higher in OP treatments, their occurrence could not be attributed to OP exposure. In addition, TOs did not seem to impair male gonad development and functionality since normal spermatogenesis was observed in testes of OP-treated fish. These results indicate that E2 occurring in the South American aquatic environment may affect male reproductive development and pose a risk for wild C. dimerus, especially under prolonged exposure, while the effects of weaker xenoestrogens such as OP would be negligible for gonad development in this species. As illustrated by this study, the natural occurrence of TOs indicates that conclusions concerning the causes of this phenomenon must be drawn with care.